1997
DOI: 10.1007/s004310050621
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal morbidity and mortality associated with maternal haemolysis elevated liver enzymes and low platelets syndrome

Abstract: : Before 32 weeks of gestation both respiratory and cardiovascular morbidity and intra-uterine growth retardation associated with HIP is further aggravated by a maternal HELLP syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
22
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 8 publications
4
22
0
Order By: Relevance
“…Data regarding neonatal BP in infants born to mother with HELLP are scarce. We are aware of one study showing HELLP to be associated with a higher need for volume expansion and a trend toward more hypotension on day 1 in preterm infants (39). Our results point in the same direction and may provide a link between HELLP syndrome and adverse outcome in preterm infants (40), although data concerning the latter are conflicting.…”
Section: Discussionsupporting
confidence: 58%
“…Data regarding neonatal BP in infants born to mother with HELLP are scarce. We are aware of one study showing HELLP to be associated with a higher need for volume expansion and a trend toward more hypotension on day 1 in preterm infants (39). Our results point in the same direction and may provide a link between HELLP syndrome and adverse outcome in preterm infants (40), although data concerning the latter are conflicting.…”
Section: Discussionsupporting
confidence: 58%
“…Dötsch et al [18] reported that before 32 weeks of gestation, both respiratory and cardiovascular morbidity and IUGR associated with preeclampsia are further aggravated by a maternal HELLP syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies have suggested that severe maternal preeclampsia is associated with a high incidence of neonatal hypotension. 19,20 Those studies did not exclude the possibility that the increased incidence of neonatal hypotension in infants born to mother with preeclampsia might have resulted from lower birth weight or fetal exposure to magnesium sulfate. Nonetheless, preeclampsia is an attractive primary etiology of neonatal hypotension as preeclampsia tends to cause intrauterine growth retardation and to result in fetal exposure to magnesium sulfate.…”
Section: Discussionmentioning
confidence: 99%
“…10 Other investigators have linked neonatal hypotension to an increased risk of central nervous system morbidities, such as intraventricular hemorrhage, 11,12 white matter injury, 13 poor neurodevelopmental outcome 14,15 and threshold retinopathy of prematurity. 16 The etiology of neonatal hypotension is likely multifactorial, 17,18 but recently severe preeclampsia 19,20 has been suggested to be a contributing factor. These studies did not define the diagnostic criteria for neonatal hypotension, nor the age of diagnosis.…”
Section: Introductionmentioning
confidence: 99%